Simultaneous optical interrogation of multiple tuning fork resonators using range-resolved interferometry - Kissinger, Thomas; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2017)
In a proof-of-principle experiment, the vibrations of a set of three tuning folk resonators are simultaneously interrogated along a single optical beam using range-resolved interferometry. Measurements with noise standard deviations in the nm levels over bandwidths of many kHz are possible. In addition, a high degree of environmental noise rejection is inherently achievable because only differential measurements between the vibrating tuning folk prong pairs are evaluated. Employing only highly coherent, robust and cost-effective diode lasers, this approach could be useful for a wide range of mechanical sensor interrogation tasks.
Keywords: Optical interferometry; Optical sensors; Mechanical sensors; Sensor systems and applications